Profiling Hand Hygiene Adherence in an Outpatient Clinic Setting - Nur Inayah Rauf; Asrar As (CV. Global Health Publication, 2025)
Infection prevention and control (IPC) represents a critical priority in healthcare delivery, with hand hygiene serving as a key quality indicator. This study aimed to profile hand hygiene compliance at Clinic X in Makassar City. A descriptive cross-sectional study was conducted involving 32 healthcare staff, including clinicians, allied health professionals, and support staff, selected through total sampling. Data collection employed direct observation using a standardised checklist based on the WHO